2018
DOI: 10.3390/catal8100429
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplasmon–Semiconductor Hybrid for Interface Catalysis

Abstract: We firstly, in this review, introduce the optical properties of plasmonic metals, and then focus on introducing the unique optical properties of the noble metal–metal-oxide hybrid system by revealing the physical mechanism of plasmon–exciton interaction, which was confirmed by theoretical calculations and experimental investigations. With this noble metal–metal-oxide hybrid system, plasmonic nanostructure–semiconductor exciton coupling interactions for interface catalysis has been analyzed in detail. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 111 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…Time resolved spectroscopy, at the femto- and picosecond scales, has been used for a few decades now to study excited charge carriers and charge transfer of materials . It was initially developed to study molecules and then extended to colloidal systems (nanoparticles) and polycrystalline materials. Information can be obtained related to interfacial charge transfer between semiconductors and between semiconductors and metals .…”
mentioning
confidence: 99%
“…Time resolved spectroscopy, at the femto- and picosecond scales, has been used for a few decades now to study excited charge carriers and charge transfer of materials . It was initially developed to study molecules and then extended to colloidal systems (nanoparticles) and polycrystalline materials. Information can be obtained related to interfacial charge transfer between semiconductors and between semiconductors and metals .…”
mentioning
confidence: 99%
“…In the future, plasmon-exciton interaction can promote efficiency and probability for plasmon-driven chemical reactions. Detailed information can be obtained from References [8,14,18,19,[53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the hydration layer was the root cause of the difference in photoreaction rate constants of the reactants and product. Studies showed that, in order for the reaction to better proceed, the nitro 4NBT group should be reduced, and protonation is needed to produce reaction intermediates [50][51][52][53][54]. In addition, the protons that came from the hydration layer on the Au surface were needed to limit the photoreaction rate [35][36][37][38][39].…”
Section: Competition Between Reaction and Degradation Pathways In Plamentioning
confidence: 99%
“…Based on local surface plasmon resonance (LSPR), surface-enhanced Raman scattering (SERS) has been investigated intensively and widely applied since 1974 [1][2][3][4]. The electric field enhancement of Raman signals can reach 10 8 -10 11 [5][6][7], while chemical enhancement can only reach 10 2 -10 3 [8][9][10].…”
Section: Introduction Of Tip-enhanced Raman Spectroscopy (Ters)mentioning
confidence: 99%